Two-Year Outcomes of a Randomized, Family-Based Substance Use Prevention Trial for Asian American Adolescent Girls - Fang, Lin (2012)
Asian Americans have been largely ignored in the prevention outcome literature. In this study, we tested a parent-child program with a sample of Asian American adolescent girls and their mothers, and evaluated the program’s efficacy on decreasing girls’ substance use, and modifying risk and protective factors at individual, family, and peer levels. One hundred and eight Asian American mother-daughter dyads recruited through online advertisements and from community service agencies were randomly assigned to an intervention arm (n = 56) or to a test-only control arm (n = 52). The intervention consisted of a nine-session substance abuse prevention program, delivered entirely online. Guided by family interaction theory, the prevention program aimed to strengthen the quality of girls’ relationships with their mothers while increasing girls’ resilience to resist substance use. Intent-to-treat analyses showed that at 2-year follow-up, intervention-arm dyads had significantly higher levels of mother-daughter closeness, mother-daughter communication, maternal monitoring, and family rules against substance use compared to the control-arm dyads. Intervention-arm girls also showed sustained improvement in self-efficacy and refusal skills, and had lower intentions to use substances in the future. Most important, intervention-arm girls reported fewer instances of alcohol and marijuana use, and prescription drug misuse relative to the control-arm girls. The study suggests that a culturally generic, family-based prevention program was efficacious in enhancing parent-child relationships, improving girls’ resiliency, and preventing substance use behaviors among Asian American girls.